Three-Dimensional In Vitro Cell Culture Models for Efficient Drug Discovery: Progress So Far and Future Prospects - Shaimaa M. Badr-Eldin; Hibah M. Aldawsari; Sabna Kotta; Pran Kishore Deb; Katharigatta N. Venugopala (MDPI AG, 2022)
Despite tremendous advancements in technologies and resources, drug discovery still remains a tedious and expensive process. Though most cells are cultured using 2D monolayer cultures, due to lack of specificity, biochemical incompatibility, and cell-to-cell/matrix communications, they often lag behind in the race of modern drug discovery. There exists compelling evidence that 3D cell culture models are quite promising and advantageous in mimicking in vivo conditions. It is anticipated that these 3D cell culture methods will bridge the translation of data from 2D cell culture to animal models. Although 3D technologies have been adopted widely these days, they still have certain challenges associated with them, such as the maintenance of a micro-tissue environment similar to in vivo models and a lack of reproducibility. However, newer 3D cell culture models are able to bypass these issues to a maximum extent. This review summarizes the basic principles of 3D cell culture approaches and emphasizes different 3D techniques such as hydrogels, spheroids, microfluidic devices, organoids, and 3D bioprinting methods. Besides the progress made so far in 3D cell culture systems, the article emphasizes the various challenges associated with these models and their potential role in drug repositioning, including perspectives from the COVID-19 pandemic.